Potencial produtivo e nutricional de cultivares de milheto sob doses de nitrogênio em diferentes alturas pré-corte - Corrêa, Daniel Staciarini (2015)
The effect of nitrogen doses and pre-cutting heights on dry matter production and nutritional value of millet cultivars were evaluated. Two sources of nitrogen: urea or ammonium sulfonitrate (ASN) treated with nitrification inhibitor were evaluated separately. The cultivars used were ADR 500; BRS 1501 and ADR 8010. Pre-cut heights were 0.70; 0.80 and 0.90 m, with a 0.20 m residual height. Nitrogen rates were 0; 45; 90 or 180 kg ha-1. For each cultivar and nitrogen source, the experiment was designed in randomized blocks in a 4 x 3 factorial scheme (4 doses of N x 3 pre-cutting heights) with three replications (blocks). Data were submitted to analysis of variance and means were compared by Tukey test at 5% probability. Regression analysis was performed for the production of dry matter of each cultivar. The field experiment was conducted in the Department of Animal Production EVZ / UFG, in situ degradability assay and chemical analyzes were carried out at PUC Goiás’ Faculdade de Zootecnia. The dry matter and ashes were determined in greenhouse and muffle, respectively. The crude protein (CP) was determined by the Kjeldahl method, the insoluble neutral (NDF) and acid (ADF) detergent fiber and lignin by sequential method. The ether extract (EE) was determined by the Soxhlet method and total carbohydrates (TC) by the equation proposed by Sniffen (1992). The Orskov and McDonald (1979) degradability equations were used, with adaptations made by Sampaio (1988). The evaluation times were 0; 12; 24; 48 and 96 hours. Related to pre-cut heights one may conclude that millet cut at 0.70 and 0.80 m high showed low dry matter levels, which affect the DM intake of animals while cutting at 0.90 m offered satisfactory content of this parameter. Regarding the use of urea as a nitrogen source, it was observed that the cultivars showed high levels of total carbohydrates and ether extract, indicating high energy density of the forage, which helps to offset the negative effects of high NDF contents presented. Nitrogen fertilization increased the CP content and promoted increased productivity of the cultivars, especially when harvested at 0.90 m. The fertilization with 180 kg ha-1 of nitrogen (urea) improved the nutritional value (composition and degradability) from cultivars except that of the cultivar ADR 500 managed in the pre-cut height of 0.80 m. Pearl millet showed high soluble fraction of NDF, which compensates the intake inhibition effect that this fraction has on the animal consumption. Regarding the use of ammonium sulfonitrate treated with nitrification inhibitor, results showed that there was an increase in productivity, but possible toxic effects were observed at lower doses (45 and 90 kg N ha-1), revealed by the low protein content and high TC and NDF presented under these doses. Nitrogen fertilization with nitrification inhibitor at high doses increased the dry matter, crude protein and neutral detergent fiber degradability of millet handled at 0.90 m. The combination of fertilization with doses of 45 and 90 kg N ha-1 (ASN) with nitrification inhibitor, with the management of millet at 0.70 or 0.80 m did not favor the nutritional quality of forage indicating that in these treatments the relationship between the availability of nitrogen in ammonium and nitrate forms may have been detrimental to the plants.